Determinants of the industrial location in Peru, 1963-1974 - Rivera Mariscal, Gonzalo (Pontificia Universidad Católica del Perú, 2025)
The present study responds to the following question: What factors determined the location of manufacturing industries in Peruvian regions for the years 1963 and 1974? Using the data of the Economic Censuses conducted in 1963 and 1974 by the Peruvian government, we evaluate the factors that influenced the location decisions. For this aim, we apply the methodology proposed by Midelfart-Knarvik et al. (2000, 2001), which integrates in a model the factors that the Heckscher- Ohlin (H-O) and the New Economic Geography (NEG) theories consider important to explain industrial location decisions. Among them, they consider the influence of the regional endowment of resources and the intensity of their use in industries (H-O theory), as well as the influence of the market potential and the backward or forward linkages between industries or the economies of scale in industries (NEG theory). Our findings indicate that for this period of analysis in Peru, the factors related to agricultural endowment, electrical energy, financial capital (components related to the H-O theory), backward linkages and the economies of scale (components related to the NEG theory) were influential in determining the industrial location decisions of the manufacturing sector across regions. The results also indicate that the two components associated with the NEG theory have the highest weighted impact on manufacturing location decisions. Another relevant aspect is that our findings allow us to partially understand the agglomeration of industries in some regions, particularly in the capital of the country, Lima.
Keywords: Industrial location; Regional economics; Factor endowments; New economic geography; Economic history of Peru; https://purl.org/pe-repo/ocde/ford#5.02.01